2018
DOI: 10.1002/mar.21111
|View full text |Cite
|
Sign up to set email alerts
|

Value co‐creation in online healthcare communities: The impact of patients’ reference frames on cure and care

Abstract: The gradual transition of health care toward businesses during the past 50 years has converted passive patients into active customers. In our digital society, patients increasingly use online health communities to satisfy complex needs that healthcare professionals leave unmet, including the creation of cure‐oriented (i.e., functional) and care‐oriented (i.e., emotion) value. This research investigates patients’ reference frames (self versus other) as an information processing mechanism and their impact on val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Yang et al mainly explored how OHCs can improve treatment efficiency from the perspective of patients’ satisfaction. Sarah et al [16] proposed that physicians are required to actively communicate with patients in OHCs to improve patients’ satisfaction. Petrič et al [17] found that social process, such as communication in OHCs, can affect the relationship between patients and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al mainly explored how OHCs can improve treatment efficiency from the perspective of patients’ satisfaction. Sarah et al [16] proposed that physicians are required to actively communicate with patients in OHCs to improve patients’ satisfaction. Petrič et al [17] found that social process, such as communication in OHCs, can affect the relationship between patients and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Further Frow et al (2016) and McColl-Kennedy et al (2012) when exploring value co-creation practices in online health communities, called for further research of value co-creation practices in other contexts. Although OCs are recognised as value co-creation entities (Mein Goh et al, 2016), which can empower actors (Cova and Salle, 2008), many studies (Mein Goh et al, 2016;van Oerle et al, 2018) have neglected the importance of value co-destruction (Plé and Chumpitaz C aceres, 2010). In addition, previous studies have explored the purposes (Nimrod, 2010) and benefits (Kamalpour et al, 2020) of joining OCs for older adults but are yet to explore the value co-creation and value co-destruction practices of older adults in OCs.…”
Section: Older Adults Online Communities and Value Co-creation Practicesmentioning
confidence: 99%
“…Therefore, patients and caregivers are the main beneficiaries of ubiquitous of value within OHCs. In essence, OHCs provide an opportunity for actors such as patients, physicians, caregivers, and nurses to share their health information and contribute in the value co-creation process within and across ecosystem levels (Bidar et al 2017;Courtney 2013;Van Oerle et al 2018).…”
Section: Australasian Conference On Information Systemsmentioning
confidence: 99%